Zeit, die Details einer besseren Elementarschadenversicherung zu diskutieren - Christian Gross; Gert G. Wagner (Wirtschaftsdienst, 2023)
Elementarschäden an Immobilien werden klimabedingt zunehmen, aber noch immer sindin Deutschland nicht alle Wohnimmobilien gegen Elementarschäden versichert. Sie sindaber überall zu tragbaren Prämien versicherbar. Die zentralen Parameter, die es zu regelngilt, sind der Abdeckungsgrad verschiedener Elementarereignisse durch die Versicherung,die Höhe des Selbstbehalts bei einer Basisversicherung, staatliche Hilfen zur Tragung desSelbstbehalts, der Umgang mit bestehenden Klumpenrisiken und eine Stop-Loss-Regelung. – – Damage to residential buildings caused by natural disasters will increase as climate change progresses. However, in Germanynot all buildings are insured against it. This article gives an overview on the current debate in Germany on how to improve the commonstate of insurance. We present new empirical evidence on the acceptance of natural disaster insurances and outline the key parametersthat should be subject to regulation. This includes the types of natural disasters that should typically covered by such an insurance, thelevel of the deductible to be paid by the household, state support for paying off the deductible, ways to deal with risk clusters that singleinsurers might face, as well as the specification of a stop-loss threshold to cap the insurers' financial risks.
Keywords: D18; G22; G28; H84; 330; Immobilien; Elementarschadenversicherung; Deutschland; Immobilien; Elementarschadenversicherung; Deutschland